Successful Treatment of Anogenital Wart with a Topical Vitamin D3 Derivative in an Infant - Tomoko Rind; Naoki Oiso; Akira Kawada (Karger Publishers, 2010)
Anogenital warts are an infectious disorder of the anogenital lesion caused by one or more human papilloma viruses. Verruca is commonly treated with freezing with liquid nitrogen, laser therapy or application of imiquimod. Such ablative treatment may cause pain and scars on the anogenital lesion. We herein report an infant case of anogenital wart which was successfully treated with a topical vitamin D3 derivative. Topical application of a vitamin D3 derivative may be an alternative therapy for anogenital warts in infants.